2016
DOI: 10.1093/nar/gkw745
|View full text |Cite
|
Sign up to set email alerts
|

Reactive sulfur species regulate tRNA methylthiolation and contribute to insulin secretion

Abstract: The 2-methylthio (ms2) modification at A37 of tRNAs is critical for accurate decoding, and contributes to metabolic homeostasis in mammals. However, the regulatory mechanism of ms2 modification remains largely unknown. Here, we report that cysteine hydropersulfide (CysSSH), a newly identified reactive sulfur species, is involved in ms2 modification in cells. The suppression of intracellular CysSSH production rapidly reduced ms2 modification, which was rescued by the application of an exogenous CysSSH donor. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Studies have found that low concentrations (nM range) of H 2 S maintained ETC function that may have been mediated by the sulfide: quinone reductase and other enzymes that oxidize sulfides to thiosulfate (Grieshaber and Völkel, 1998;Griesbeck et al, 2002;Goubern et al, 2007;Ono et al, 2014;Szabo et al, 2014;Hine et al, 2015). In addition, another study found that CysSSH may be partly responsible for endogenous formation of iron-sulfur clusters (Takahashi et al, 2017). Our various studies suggest that CSE, CBS and 3-mercapopyruvate sulfur transferase are not primary H 2 S sources in mitochondria in different mammalian cell lines and in vivo in mice (Nishida et al, 2012;Morikawa et al, 2012;Ono, et al, 2014;Shirozu et al, 2014;Nakano et al, 2015;Yadav et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Studies have found that low concentrations (nM range) of H 2 S maintained ETC function that may have been mediated by the sulfide: quinone reductase and other enzymes that oxidize sulfides to thiosulfate (Grieshaber and Völkel, 1998;Griesbeck et al, 2002;Goubern et al, 2007;Ono et al, 2014;Szabo et al, 2014;Hine et al, 2015). In addition, another study found that CysSSH may be partly responsible for endogenous formation of iron-sulfur clusters (Takahashi et al, 2017). Our various studies suggest that CSE, CBS and 3-mercapopyruvate sulfur transferase are not primary H 2 S sources in mitochondria in different mammalian cell lines and in vivo in mice (Nishida et al, 2012;Morikawa et al, 2012;Ono, et al, 2014;Shirozu et al, 2014;Nakano et al, 2015;Yadav et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Indeed, recent study of MiaB, the bacterial CDKAL1 homologue proteins, has shown that the sulphur atom of the 2‐methylthio modification was likely derived from extra sulphur atoms attaching to the [4Fe‐4S] clusters . In line with these findings, Takahashi et al reported that human CDKAL1 contains extra sulphur atoms in the [4Fe‐4S] cluster‐binding domain, which are enzymatically transferred to tRNA Lys(UUU), (Figure ). The authors also identified the enzymes that are responsible for the production of extra sulphur atoms and showed that insulin secretion was reduced in mice with a deficiency of the sulphur‐producing enzyme.…”
Section: Regulatory Mechanism Of Cdkal1mentioning
confidence: 62%
“…The methyl group of 2‐methylthio modification is derived from SAM, whereas the origin of the thio (sulphur) group has been unclear. Because both [4Fe‐4S] clusters and cysteine residues are highly sensitive to oxidative conditions, it is predicted that CDKAL1‐mediated 2‐methylthio modification might be regulated by the intracellular redox state. Indeed, recent study of MiaB, the bacterial CDKAL1 homologue proteins, has shown that the sulphur atom of the 2‐methylthio modification was likely derived from extra sulphur atoms attaching to the [4Fe‐4S] clusters .…”
Section: Regulatory Mechanism Of Cdkal1mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mutations of the human protein CDK5 regulatory subunit associated protein 1-like 1 (Cdkal1), the enzyme responsible for the ms 2 modification of N 6 -threonylcarbamoyladenosine, t 6 A 37 (Figure 2a), are associated with lack of processing of proinsulin and decreased secretion of the mature insulin [183]. Interestingly, a new reactive species, cysteine hydropersulfide (CysSSH) has been reported as substrate and thio-donor for this enzyme with suppression of CysSSH production associated with a decrease in insulin secretion [184]. At least one of the purine-37 modification enzymes, human tRNA isopentenyltransferase, TRIT1, has a direct consequence on human health for it is a tumor suppressor [181], whereas modification of G 37 , 3 -adjacent to A 36 in phenylalanine tRNAs, may actually promote frameshifting in some codon contexts [185].…”
Section: Modifications At Position 37mentioning
confidence: 99%